Metode Akupresure untuk Mengurangi Dismenorea Remaja - Nafi’ah; Retno Ginanjar; Anggraeni Indri Hapsari; Inayatul Hidayah; Kurniawati Tri Utami; Reni Mustikaningrum; Rizky Febria Suseno; Vistra Veftisia (Universitas Ngudi Waluyo, 2025)
Dysmenorrhea, or menstrual pain, is a common complaint experienced by adolescent girls and can interfere with their daily activities, both at school and in social settings. This issue is often not addressed optimally due to the limited knowledge adolescents have about non-pharmacological approaches to managing menstrual pain. Acupressure is known as an effective and safe non-pharmacological method for pain management. This community service program aimed to increase adolescents’ knowledge about dysmenorrhea and to teach acupressure techniques as an alternative approach. The activity was conducted simultaneously on May 31, 2025, in three locations: Loragung Village (Pekalongan), Girimukti Village (Penajam Paser Utara), and Tanjung Redeb Sub-district (Berau), involving 29 female adolescents. The methods used included health education, small group discussions, hands-on acupressure practice, and evaluation through pre-test and post-test assessments. The results showed a significant improvement in participants’ knowledge, with a statistical significance value of < 0.001. This program proved to be effective and is recommended for sustainable replication in other communities. Abstrak Dismenore atau nyeri haid merupakan keluhan umum yang dialami oleh remaja perempuan dan dapat mengganggu aktivitas sehari-hari, baik di sekolah maupun di lingkungan sosial. Masalah ini seringkali tidak ditangani secara optimal karena minimnya pengetahuan remaja tentang penanganan nyeri haid yang non-farmakologis. Metode akupresur dikenal sebagai salah satu penanganan non-farmakologis yang efektif dan aman. Kegiatan pengabdian masyarakat ini bertujuan untuk meningkatkan pengetahuan remaja tentang dismenore dan keterampilan akupresur sebagai alternatif pengelolaannya. Kegiatan dilaksanakan serempak pada 31 Mei 2025 di tiga lokasi: Desa Loragung (Pekalongan), Desa Girimukti (Penajam Paser Utara), dan Kelurahan Tanjung Redeb (Berau), melibatkan 29 remaja perempuan. Metode yang digunakan mencakup edukasi, diskusi kelompok kecil, praktik akupresur, serta evaluasi menggunakan pre-test dan post-test. Hasil menunjukkan peningkatan signifikan pengetahuan peserta dengan nilai signifikansi < 0,001.